2022
DOI: 10.1186/s12967-022-03411-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell sequencing analysis reveals gastric cancer microenvironment cells respond vastly different to oxidative stress

Abstract: Gastric cancer is a common type of gastrointestinal malignant tumor in China. The mechanism of the development and progression of gastric cancer remains the continuing research focus. The tumor microenvironment plays an important role in the development and progression of tumors. The present study used single-cell sequencing data to characterize the microenvironment of gastric cancer, investigate the effects of oxidative stress on gastric cancer microenvironmental cells through the comparison between cancer ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Recent single cell RNA-sequencing analysis of gastric cancers shows that HBA1 is overexpressed in gastric cancer cells. Importantly, patients with high tumour HBA1 expression led to poor overall survival supporting our findings in CRLM [ 37 ]. The contributions of IMPDH2 in CRC progression is well established.…”
Section: Discussionsupporting
confidence: 85%
“…Recent single cell RNA-sequencing analysis of gastric cancers shows that HBA1 is overexpressed in gastric cancer cells. Importantly, patients with high tumour HBA1 expression led to poor overall survival supporting our findings in CRLM [ 37 ]. The contributions of IMPDH2 in CRC progression is well established.…”
Section: Discussionsupporting
confidence: 85%
“…Combination therapies to combat chemotherapy resistance have been extensively studied in clinical trials, while cancer treatment strategies that modulate ROS to modify the tumor microenvironment urgently need more in-depth research ( 75 ). Research has shown that oxidative stress is increased in T cells and decreased in mucous cells in the gastric cancer microenvironment, while TRIM62, MET and HBA1, which are associated with oxidative stress, may be biomarkers reflecting the prognosis of gastric cancer ( 76 ). Selective targeting of ROS-mediated signal pathways, including the role of tracer elements, systems regulated by the stress response transcription factor Nrf2 and nuclear factor-κB, as well as environmental factors, may increase the precision of the redox agents used ( 77 ).…”
Section: Natural Products Possess Anti-tumor Functionmentioning
confidence: 99%
“…We obtained the following items to fully assess the OS-related functions in IVD tissues: “GO_RESPONSE_TO_OXIDATIVE STRESS,” “GO_REGULATION_OF_RESPONSE_TO_OXIDATIVE_STRESS,” “GO_CELL_DEATH_IN_RESPONSE_TO_OXIDATIVE_STRESS,” and “GO_CELLULAR_OXIDANT_DETOXIFICATION,” as Yu et al. described ( 41 ). OS-related scores of different cell populations were calculated to evaluate these OS functions.…”
Section: Methodsmentioning
confidence: 99%